Reference biomechanical parameters and natural asymmetry among runners across the age spectrum without a history of running-related injuries - Vincent, Heather K.; Popp, Reed; Cicilioni, Orlando; Vincent, Kevin R.; Pezzullo, Lydia; Martenson, Matthew; Nixon, Ryan M. (Frontiers in Sports and Active Living, 2025)
IntroductionRunning biomechanics and expected mechanical asymmetries with no history of running-related injuries, and (2) determine whether age influenced gait parameter asymmetry.MethodsThis cross-sectional study included 250 runners were used to test age effects on biomechanical variables and asymmetry outcomes. Effect sizes of age brackets were determined for runner characteristics and biomechanical variables.ResultsRunners aged 55 years had the slowest velocity and 1.7%–4% slower occurred in ankle flexion moments, ankle and knee frontal excursions, and peak VALR (range, 12.1%–33.8% different between right and left limbs).DiscussionGiven that we did not find consistent effects. These data can help inform reference ranges of normative biomechanical metrics and guide clinicians in gait retraining and performance targets across the age spectrum.